ANALISIS PERBEDAAN FUNGSI PARU PADA PEKERJA BERDASARKAN KADAR DEBU DI PT. BOGOWONTO PRIMALARAS SEMARANG - Shadna Sari; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
One of the negative impacts of the wood processing industry is the air pollution produced by wood dust from the processing of raw materials or the end product of industrial products. Workers and  communities around the industry are potential to be exposed to the dust generated by wood  production. The study aimed to analyze the difference of lung function  (prediction value of FVC and FEV1) on workers based on total dust concentration at PT. Bogowonto Primalaras Semarang. This research used observational analytic research with cross-sectional approach. 36 workers as respondents taken by purposive sampling from 110 people as  the popullation. The results of dust concentration by measurement using High Volume Air Sampler (HVAS) (Finishing Coating=6,46 mg/m3, Finishing Raw=5,67 mg/m3, Flush Door=2,33 mg/ m3. While the result of lung function measurement there are 69,4% of workeres have lung function disorder (Light Restriction=41,7%, Middle Restriction=25,0%, Heavy Restriction=2,8%) average value (μ FVC=69.63, σ FVC=12.8 and μ FEV1= 78.88, σ FEV1=14.7). Data were analyzed using one way anova test with (α=0,05). The statistical test result of FVC prediction value (p=0,853) and FEV1 prediction value (p=0,814) meaning no difference (prediction value of FVC and FEV1) on workers based on total dust concentration at PT Bogowonto Primalaras Semarang and dust concentration do not affect the insidence of lung function disorder. It is recommended that the company doing replacement on workers and improve the supervision of PPE (mask) use on workers continually.